Splicing alterations contributing to cancer hallmarks in the liver: central role of dedifferentiation and genome instability - Jimenez, Maddalen; Arechederra, María; Ávila, Matías A.; Berasain, Carmen (Translational Gastroenterology and Hepatology, 2018)
Hepatocellular carcinoma (HCC) is a major cause of cancer-related death worldwide. HCCs are molecularly heterogeneous tumors, and this complexity is to a great extent responsible for their poor response to conventional and targeted therapies. In this review we summarize recent evidence indicating that imbalanced expression of mRNA splicing factors can be a relevant source for this heterogeneity. We also discuss how these alterations may play a driver role in hepatocarcinogenesis by impinging on the general hallmarks of cancer. Considering the natural history of HCC, we focused on two pathogenic features that are characteristic of liver tumors: chromosomal instability and phenotypic de-differentiation. We highlight mechanisms connecting splicing derangement with these two processes and the enabling capacities acquired by liver cells along their neoplastic transformation. A thorough understanding of the alterations in the splicing machinery may also help to identify new HCC biomarkers and to design novel therapeutic strategies.